Foucault - Deleuze, Gilles 1925-1995 (London Bloomsbury, 2006)
Giles Deleuze (1925-1995) was Professor of Philosophy at the University of Paris VIII. He is a key figure in poststructuralism and one of the most influential philosophers of the twentieth century. In Foucault, Deleuze presents one of the most incisive and productive analyses of the work of Michel Foucault. This is a crucial examination of the philosophical foundations and principal themes of Foucault's work, providing a rigorous engagement with Foucault's views on knowledge, punishment, power, and the nature of subjectivity.